2018
DOI: 10.1063/1.5030855
|View full text |Cite
|
Sign up to set email alerts
|

Transient dynamics of strongly coupled spin vortex pairs: Effects of anharmonicity and resonant excitation on inertial switching

Abstract: Spin vortices in magnetic nanopillars are used as GHz oscillators, with frequency however essentially fixed in fabrication. We demonstrate a model system of a two-vortex nanopillar, in which the resonance frequency can be changed by an order of magnitude, without using high dc magnetic fields. The effect is due to switching between the two stable states of the vortex pair, which we show can be done with low-amplitude fields of sub-ns duration. We detail the relevant vortex-core dynamics and explain how field a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
2
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 30 publications
(33 reference statements)
1
2
0
1
Order By: Relevance
“…The excitation time obtained here, for the electron-hole mass-vortex at , is of the order of the decoupling time of the vertically-stacked pair of spin-vortices with core-core bound states, predicted theoretically in previous studies [52,53] and observed experimentally in a recent study [54]. Another physical observation concerns the construction of the electron band mass-vortex presented in Figures 1 and 7.…”
Section: Dirac's Dispersion Law In Graphenesupporting
confidence: 72%
“…The excitation time obtained here, for the electron-hole mass-vortex at , is of the order of the decoupling time of the vertically-stacked pair of spin-vortices with core-core bound states, predicted theoretically in previous studies [52,53] and observed experimentally in a recent study [54]. Another physical observation concerns the construction of the electron band mass-vortex presented in Figures 1 and 7.…”
Section: Dirac's Dispersion Law In Graphenesupporting
confidence: 72%
“…Свойства вихревого СТНО, когда магнитный вихрь существует в каждом из магнитных слоев [8][9][10][11][12][13][14], в значительной степени зависят от полярности вихрей. Теоретически показано, что с помощью спин-поляризованного тока можно возбудить гиротропные колебания магнитостатически связанных вихрей с постоянной частотой, которая может меняться при приложении магнитного поля [12,13].…”
unclassified
“…The properties of a vortex STNO, when the magnetic vortex exists in each of the magnetic layers [8][9][10][11][12][13][14], largely depend on the polarity of the vortices. It is theoretically shown that with the help of a spin-polarized current it is possible to excite gyrotropic oscillations of magnetostatically coupled vortices with a constant frequency, which can change when the magnetic field is applied [12,13].…”
mentioning
confidence: 99%